Networking to accelerate the pace of SME innovations - Firouze Pourmand Hilmersson; Mikael Hilmersson (Journal of Innovation & Knowledge (JIK), 2021)
This paper investigates how the time to a firm's first innovation affects the continued pace of innovation and how the networking behaviour of the firm moderates this relationship. In doing so, the paper develops a relationship among three constructs: time to innovation, pace of innovation, and networking. We draw on resource accumulation theory and network theories to develop our hypotheses, which are tested on a sample of 203 SMEs. The results indicate that the innovation pace of a firm depends on the capabilities developed. By developing innovation capabilities at an early age, firms are likely to drive market changes instead of being challenged by them. Firms that lag in the innovation process can compensate for this by actively networking for resources and capabilities.
Keywords: 650; Innovation; Pace; SME; Speed